Option the secret life of Steve Jobs : a parody (Philadelphia Da Capo Press, 2008)
A parody of Silicon Valley culture chronicles the struggles, triumphs, celebrity encounters, political hobnobbing, and counterintuitive management philosophy of Fake Steve Jobs, in a fictional memoir.
Keywords: Jobs, Steve, -- 1955-2011 -- Humor; Apple Computer, Inc. -- Humor; Executives -- Fiction; Santa Clara Valley (Santa Clara County, Calif.) -- Fiction